2008
DOI: 10.1111/j.1399-5618.2007.00501.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictors of unrecognized bipolar I and II disorders

Abstract: Correct diagnosis of BD I is related to the severe phases of illness leading to hospitalizations. In BD II, the illness factors may not be as important as time elapsed in treatment, a factor that often leads to a delay in diagnosis or none at all. Excessive reliance on typical and cross-sectional presentations of illness likely explain the non-recognition of BD. The challenge for correctly diagnosing bipolar patients is in outpatient settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 38 publications
5
15
0
Order By: Relevance
“…This is in line with previous studies showing that patients with co-occurring mental illness and substance use disorders are more likely to use health care services than patients with only 1 disorder (Jacobi et al, 2004;Regier et al, 1993;Urbanoski et al, 2007;Wu et al, 1999). It also converges with findings of higher rates of substance use disorders in patients with recognized BD compared with patients with unrecognized BD (Mantere et al, 2008).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This is in line with previous studies showing that patients with co-occurring mental illness and substance use disorders are more likely to use health care services than patients with only 1 disorder (Jacobi et al, 2004;Regier et al, 1993;Urbanoski et al, 2007;Wu et al, 1999). It also converges with findings of higher rates of substance use disorders in patients with recognized BD compared with patients with unrecognized BD (Mantere et al, 2008).…”
Section: Discussionsupporting
confidence: 78%
“…Among those who receive this treatment, many experience long delays from illness onset to correct diagnosis (Berk et al, 2007;Kessing, 2005;Lish et al, 1994) and/or initiation of adequate treatment (Altamura et al, 2009;Baethge et al, 2003b;Post et al, 2003). Female patients (Baldessarini et al, 2007;Kessing, 2005;Mantere et al, 2008), patients with an earlier onset of the BD (Berk et al, 2007;Kessing, 2005;Larsson et al, 2009;Suominen et al, 2007), and patients with BD II rather than BD I disorder (Baldessarini et al, 2007;Mantere et al, 2008) seem to have longer delays. Whereas long durations of untreated illness is found to be clearly associated with a more severe course and outcome in schizophrenia (Marshall et al, 2005;Melle et al, 2008), it is more disputed whether treatment delays lead to a poorer outcome in BD (Baethge et al, 2003a;Baldessarini et al, 2007).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…In general, RCBD has been associated with worse disease outcome 9,10 and more severe disability. 7,11,12 More specifically, many factors have been described to be associated with RC, such as female gender, 5,13 earlier age at onset, 6,12 increased risk for suicide, 13,14 predominance of depression, 15,16 hypothyroidism, 6,17 bipolar type II disorder, 8,18,19 and higher rates of antidepressants use. 7,20 However, some of these associations are still controversial, and many studies have been criticized regarding aspects such as lack of a uniform definition of RC and use of heterogeneous samples.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have found that the rate of missed diagnoses of bipolar disorder is fairly high, especially when a broader definition of hypomania is used than the one specified in DSM-IV. 15,16,21,[28][29][30] As a clinician, it is often the case that early in the course of treatment I am not sure if a currently depressed patient has bipolar disorder. This uncertainty occurs despite an extensive evaluation that includes the administration of a semistructured interview, a review of prior records, and an interview with an informant.…”
Section: Detecting Past Episodes Of Hypomania In Depressed Patients Amentioning
confidence: 99%